Building Human Capital : Lessons from Country Experiences – Singapore - Yusuf, Shahid (World Bank, Washington, DC, 2020)
Singapore has demonstrated that investing in human capital can have a high payoff and that nothing is impossible. Its example should inspire others to redouble their own efforts, not to replicate the model in its entirety necessarily but to take full advantage of the various lessons that can be learned from the arc of its successful development strategy. Many elements of the Singapore model are today considered conventional wisdom. While many developing countries have attempted to pursue similar strategies, few have fully succeeded in achieving similar results. This case study examines the policies, programs and processes Singapore has pursued from 1960 to the present to pull ahead of other economies. It identifies several factors that have undergirded Singapore’s successful implementation of education and health strategies. First, collecting and analyzing data to harness them for policymaking purposes. Second, able and incorruptible leaders who set high standards for themselves and others and have lived up to these standards. Third, Singapore created a meritocratic and largely non-politicized bureaucracy that could strategize, make far sighted policies, and implement them in a coordinated way. Coordinated implementation is key to delivering results. Fourth, national leadership-maintained harmony in a multi-ethnic society and proactively defused tensions. Fifth, Singapore attracted immigrants, both skilled and unskilled. Sixth, leadership mobilize domestic resources which played a critical role in financing infrastructure, housing, and other vital investments. Lastly, Singapore has never been comfortable to rest on its laurels and has always been open to ideas, eager to learn, ready to innovate, and leverage new technologies.